2011
DOI: 10.1186/1471-244x-11-48
|View full text |Cite
|
Sign up to set email alerts
|

Social support and antenatal depression in extended and nuclear family environments in Turkey: a cross-sectional survey

Abstract: BackgroundSocial support is strongly implicated in the aetiology of perinatal mental disorder: particularly the quality of the marital and family environment. Family structures are important under-researched potential modifiers. Turkey offers particular advantages for research in this area because of long-standing coexistence of Western and Middle Eastern family structures. We aimed to investigate associations between the quality of key relationships and depression in women in their third trimester of pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 32 publications
13
69
2
3
Order By: Relevance
“…Fear of pregnancy complications [AOR=3.49, CI (1.45, 8.41)] and previous abortion [AOR=2.86, CI (1.13, 7.24)] showed strong association; analogous with a prior report in Africa (Lee et al, 2007). A positive relationship between presence of chronic illness and antenatal depressive disorders was seen prior to controlling confounders but no longer existed; opposite to previous findings (Senturk et al, 2011). This might be explained by the variation in sample size and instruments.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Fear of pregnancy complications [AOR=3.49, CI (1.45, 8.41)] and previous abortion [AOR=2.86, CI (1.13, 7.24)] showed strong association; analogous with a prior report in Africa (Lee et al, 2007). A positive relationship between presence of chronic illness and antenatal depressive disorders was seen prior to controlling confounders but no longer existed; opposite to previous findings (Senturk et al, 2011). This might be explained by the variation in sample size and instruments.…”
Section: Discussioncontrasting
confidence: 54%
“…Standard survey was carried out on ten Michigan Obstetric units and the report viewed 20% prevalence rate (Marcus et al, 2003). Another study conducted among rural and urban pregnant women at Ankara antenatal settings found prevalence of 33.1% (Senturk et al, 2011). And also; a hospital based study in Hong Kong took the samples at the antenatal clinic and revealed 37% prevalence of depressive symptoms (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In general, research in Turkey has tended to confirm risk factors suggested from Western populations such as low income and socio-economic status, previous mental disorders and perceived poor child health. Lack of support from the husband and wider family has also been implicated [5, 6, 25, 26]. It is generally assumed that male gender preference is not as prominent in Turkey as in some of the low and middle income countries in which it has been previously researched; however, it has received little systematic investigation, and may well vary by region and sub-culture.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Prevalence of maternal stress has been reported 33%-37% and 5%-7% in England and Sweden, respectively. [27] This rate is also estimated to about 16.7% and 13.6% for severe and mild pregnancy stress, respectively, amongst Iranian women. [28] Given the potential buffering effects of social support on maternal stress and improving pregnancy outcomes on the one hand, and shortage of relevant studies in Iran, on the other hand, this study was performed to investigate the relationship of social support and maternal stress level among Iranian pregnant women.…”
Section: Introductionmentioning
confidence: 99%